Pengaruh Manajemen Kurikulum, Budaya Sekolah, dan Kompetensi Pedagogik Guru terhadap Kualitas Pembelajaran SMK Swasta - Nurhayati, Lilik Tursila; Murniati, Ngurah Ayu Nyoman; Ginting, Rosalina BR (Jurnal Inovasi Pembelajaran di Sekolah, 2024)
The background to this research problem is related to the quality of learning at private vocational schools in Blora Regency, namely: (1) Curriculum development must be accompanied by development of teacher competency, as the main human resource in the learning process in education units, (2) the existence of several private vocational schools. with less than optimal Learning Quality related to the new curriculum management implemented, 2) the existence of some Private Vocational Schools with less than optimal Learning Quality related to low School Culture, (3) the existence of some Private Vocational Schools with less than optimal Learning Quality related to Pedagogical Competency lowly teacher. This research aims to analyze: (1) The influence of curriculum management on the quality of learning, 2) The influence of school culture on the quality of learning, 3) The influence of pedagogical competency on the quality of learning, and 4) The influence of curriculum management, school culture and pedagogical competency together. - the same for the Quality of Learning. This research uses a quantitative correlational research approach and an ex post facto research approach. The research population was 633 private vocational school teachers in Blora Regency and the research sample was 86 teachers. The analysis of this research includes analysis of validity, reliability, normality tests, linearity tests, multicollinearity tests, and heteroscedasticity tests. Hypothesis testing includes simple regression tests and multiple regression tests using SPSS 25 for Windows. The research results show that: 1) Curriculum Management has a positive and significant effect on the Quality of Learning. This is based on the results of the partial t test, it is proven that the results of tcount ≥ ttable, namely t1 count 3.712 > t table 1.66, and the Sig (2-tailed) value 0.000 < 0.05; (2) School culture has a positive and significant effect on the quality of learning. This is based on the results of the partial t test in the table above, the calculated t2 result is 4.075 > t table 1.66 and the calculated t2 significance level is 0.000 < 0.05; (3) Pedagogical Competency has a positive and significant effect on Learning Quality. This is based on the results of the partial t test in the table above, the calculated t3 result is 3.206 > t table 1.66 and the calculated t3 significance level is 0.002 < 0.05; (4) Curriculum Management, School Culture and Pedagogical Competence simultaneously influence the Learning Quality variable, obtained by lFcount of 10.570 with a significance level of 0.000.   lWith lα = l0.05l and degrees of freedom lv1 = 115l (n(lk-3)) then we get Ftable 2.72. The calculation results show that the value lFcount > lFtable (10.570 > l2.72) and the significance value is 0.000 < 0.005.